Nursing Students’ Views on Numeracy: An Exploratory Cross-Sectional Study in Riyadh, Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2025)
Medication administration in healthcare settings demands strong mathematical skills fromhealthcare practitioners. This study investigated nursing students’ perceptions of mathematical calculations inNursing at a Saudi university in Riyadh, Saudi Arabia. Materials and Methods: A cross-sectional study wasconducted at the College of Nursing in a Saudi University, Riyadh, Kingdom of Saudi Arabia, between June andJuly 2025. The data were collected using a self-administered paper-based questionnaire of 16 items and analyzedusing the statistical package for the social science (SPSS) version 26. Results: Among the students, majoritywere male, 74% (n = 182) belonged to the baccalaureate nursing program as compared to 20.3% (n = 50) in theMasters’ nursing program. Nearly 58% of participants claimed that they studied mathematics during their nursingcourse (n = 141). While 56.9% (n = 140) perceived that their ability to perform mathematical calculations relatedto drug dosing would be important to them as future practicing nurses. One-third of the students were perceived(n = 83) to have good skills, while only 23.6% (n = 58) had excellent mathematical skills. A significant associationwas found between participant characteristics, such as age (P < 0.0001), educational level (P < 0.0001), degree(P < 0.0001), and the rating of self-reported perceptions of mathematical ability (P < 0.0001). Conclusion: Thisstudy reveals that nursing students perceive mathematical skills positively and advocate for increased emphasison medical calculations in their degree course. Furthermore, our findings underscore the importance of enhancingnursing students’ understanding of mathematical skills and their critical role in healthcare.